VHDL Modeling Of ATM To IP Conversion Chip - Chew, Beng Wah (2002)
This project involves with ATM (Asynchronous Transfer Mode) technology and a method for incorporating it into existing computer networks based on the IP (Internet Protocol) standard. The objective of this project to model a computer chip that is able to convert ATM cells into IP packets and extracts the data from these IP packets, and it must also be reversible to split the IP data packets into small ATM cells.